The relationship between Turkish high school administrators' technology leadership self-efficacies and their attitudes and competencies towards technology use in education. - KARACA, FERİDE (My University, 2022)
A correlational study was conducted to examine the relationship between high school administrators’ technology leadership self-efficacies and their attitudes and competencies towards technology use in education. The participants were 338 school administrators (67 administrators and 271 vice administrators) working in 112 high schools located in the Anatolian side of Istanbul and the data were collected through a questionnaire. According to the findings, the school administrators' technology leadership self-efficacies were all sufficient and they had positive attitudes and sufficient competencies towards using technology. In addition, there were positive relationships between school administrators' technology leadership self-efficacies, their attitudes towards the use of technology and their competencies in using technology in education. Similarly, there was a positive relationship between the attitudes and the competencies of school administrators towards using technology. Conducted with a group of school administrators, accepted as the technology leaders of the school, this study sheds light on the relationship between the necessary school administrator characteristics in technology integration processes. The present study is indeed valuable in exploring the relationship among these three critical factors influencing the school principals’ effectiveness in the technology integration process. Examining these important school administrator characteristics, this study will cast light on the ways through which creating a digital school culture by improving their leadership qualifications may become possible.
Keywords: 21st century skills; school administrators; technology leadership self-efficacies; high schools; attitudes and competencies for using technologies in education